2022
DOI: 10.1039/d2dt01181f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the thermoelectric performance of Cu3SbSe4 particles by controlling morphology using exfoliated selenium nanosheets

Abstract: Copper antimony selenide (Cu3SbSe4), a ternary Cu-based material, is a promising p-type thermoelectric material. In this study, the morphology of Cu3SbSe4 particles was controlled using the shape of Se during...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The TEM image and HRTEM image of the as-prepared CSS MPs are shown in Figure c,d. The CSS MPs exhibit an irregular triangular morphology, with an interplanar spacing of 0.3212 nm assigned to the (112) facet . The narrowing interplanar spacing, combined with the shrinkage of the unit cell presented in XRD analysis, strongly evidences extra host atom vacancies generated in the unit cell of Cu 3 SbSe 4 crystals synthesized by using the Se NW template.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The TEM image and HRTEM image of the as-prepared CSS MPs are shown in Figure c,d. The CSS MPs exhibit an irregular triangular morphology, with an interplanar spacing of 0.3212 nm assigned to the (112) facet . The narrowing interplanar spacing, combined with the shrinkage of the unit cell presented in XRD analysis, strongly evidences extra host atom vacancies generated in the unit cell of Cu 3 SbSe 4 crystals synthesized by using the Se NW template.…”
Section: Resultsmentioning
confidence: 93%
“…Kim et al reported morphology optimization of a Cu 3 SbSe 4 thin film to enhance its thermoelectric performance using exfoliated selenium nanosheets. The synthesized Cu 3 SbSe 4 nanosheets achieved a ZT value of 0.40, which was 1.41 times higher than that of Cu 3 SbSe 4 nanoparticles …”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…This inspired us to investigate other wet-chemistry approaches for the synthesis of selenide inorganic materials. Specifically, simple amines like 1,2-ethylene diamine (EDA) have been used extensively to produce thermoelectric selenides such as Cu 3 SbSe 4 and its doped derivatives at reflux conditions. , We employed a similar approach, in which elemental Na, Se, and Sb 2 Se 3 with the stoichiometry shown in eq were dispersed in EDA and examined the impact of different reaction temperatures in the formation of the desired selenide. As Na 3 SbSe 4 is soluble in EDA within the concentration range used, the supernatant was evaporated at 150 °C in an Ar atmosphere to obtain the SSE powder. 6 Na + Sb 2 Se 3 + 5 Se 2 Na 3 SbSe 4 …”
Section: Resultsmentioning
confidence: 99%